On the gravitational dual to strongly coupled fluids - Shawa, Mark Musonda Webster (Rhodes University, Faculty of Science, Department of Physics and Electronics)
This thesis discusses the prospect of finding the gravitational dual to the strongly coupled conformal fluids, with a special interest in the quark-gluon plasma. Such a task can be achieved by matching certain physical observables of two apparently different theories that are dually related owing to the fact that the same string theory can be viewed in two different ways. This is particularly useful when one of the theories is intractable while its dual is manageable. We begin by postulating a particular type of gravitational theory from which we determine graviton scattering amplitudes in a special regime of high momentum. Using the gauge"“gravity duality dictionary, the graviton scattering amplitudes can be mapped to stress-tensor correlation functions in the gauge theory. One of the outcomes of high-energy scattering experiments involving the quark-gluon plasma is stress-tensor correlator data. This thesis provides an algorithm for matching graviton scattering amplitudes with stress-tensor correlator data which, in principle, can be used to identify the gravitational dual to the quark-gluon plasma.
Keywords: Quantum gravity; String models; Gauge fields (Physics); Scattering amplitude (Nuclear physics); Quark-gluon plasma; Anti-de Sitter/Conformal Field Theory (AdS/CFT); Gauge/gravity duality